Theories of lexical semantics - Geeraerts, Dirk, 1955- (Oxford : Oxford University Press, 2010)
This text provides an introduction to the history and current state of theories of word meanings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semantics, Historical; Linguistic change